Reflecting upon teaching diversity-centered courses: dialogues between novice and veteran professors. Issue 1 (2nd January 2020) - DiGregorio, Nikki; Liston, Delores D.
ABSTRACT: Self-reflection has been demonstrated to have a positive effect on the academic growth of educators. Teachers that actively engage in self-reflection are more likely to exhibit an increased interest in the development of innovative teaching strategies, learning, and collaborative practices. This paper highlights the experiences and self-reflection of two teachers of diversity-centered courses, at very different points in their careers: one a veteran Professor of more than 20 years and one an Assistant Professor of less than 5 years. Utilizing both formal and informal feedback from students, both professors reflect on their experiences teaching diversity-centered courses. Recommendations and implications for new and established professionals and the broader community of the Scholarship of Teaching and Learning (SoTL) are discussed.